Students' Perception of Thermal Comfort Regarding Seat Selection in Lecture Room B.101 Department of Architecture, Diponegoro University, Semarang - Maheswari Laksita Laksmi Paramita; Eddy Prianto (ARCHIHUMANUM, 2026)
Thermal comfort is a crucial factor influencing students’ concentration and behavior in lecture rooms, yet uneven temperature distribution and airflow often create discomfort that affects seating preferences. This study aims to examine the relationship between students’ thermal comfort perception and their seating choices in Lecture Room B.101 at the Architecture Department, Diponegoro University. A quantitative survey method was employed by distributing questionnaires to 26 respondents, consisting of closed-ended questions and one open-ended question, and the data were analyzed descriptively. The results indicate that most students are significantly affected by the direction and airflow from the air conditioner, leading them to avoid seats near the AC unit. Respondents generally prefer sitting at positions farther from the AC to achieve better thermal, humidity, and visual comfort toward the screen. These findings show that thermal perception plays an important role in students’ adaptive behavior in choosing their seats. In conclusion, a clear relationship exists between thermal comfort and seating preferences, highlighting the need for proper airflow management and spatial layout arrangement in lecture room design to support an optimal learning environment.